L-Canavanine potentiates cytotoxicity of chemotherapeutic drugs in human breast cancer cells - Nurcahyanti, Agustina Dwi Retno; Wink, Michael (Anti-cancer agents in medicinal chemistry, 2017)
Background: Due to the high level of argininosuccinate synthase (ASS), a key enzyme for the formation of arginine from citrulline, human breast can...